A Missense Variant in KCNJ10 in Belgian Shepherd Dogs Affected by Spongy Degeneration with Cerebellar Ataxia (SDCA1). Issue 2 (1st February 2017) - Mauri, Nico; Kleiter, Miriam; Leschnik, Michael; Högler, Sandra; Dietschi, Elisabeth; Wiedmer, Michaela; Dietrich, Joëlle; Henke, Diana; Steffen, Frank; Schuller, Simone; Gurtner, Corinne; Stokar-Regenscheit, Nadine; et al.
Abstract: Spongy degeneration with cerebellar ataxia (SDCA) is a severe neurodegenerative disease with monogenic autosomal recessive inheritance in Malinois dogs, one of the four varieties of the Belgian Shepherd breed. We performed a genetic investigation in six families and seven isolated cases of Malinois dogs with signs of cerebellar dysfunction. Linkage analysis revealed an unexpected genetic heterogeneity within the studied cases. The affected dogs from four families and one isolated case shared a ∼1.4 Mb common homozygous haplotype segment on chromosome 38. Whole genome sequence analysis of three affected and 140 control dogs revealed a missense variant in the KCNJ10 gene encoding a potassium channel (c.986T>C; p.Leu329Pro). Pathogenic variants in KCNJ10 were reported previously in humans, mice, and dogs with neurological phenotypes. Therefore, we consider KCNJ10 :c.986T>C the most likely candidate causative variant for one subtype of SDCA in Malinois dogs, which we propose to term spongy degeneration with cerebellar ataxia 1 (SDCA1). However, our study also comprised samples from 12 Malinois dogs with cerebellar dysfunction which were not homozygous for this variant, suggesting a different genetic basis in these dogs. A retrospective detailed clinical and histopathological analysis revealed subtle neuropathological differences with respect to SDCA1-affected dogs. Thus, our study highlights the genetic and phenotypic complexity underlying cerebellar dysfunction in Malinois dogs and provides the basis for a genetic test to eradicate one specific neurodegenerative disease from the breeding population. These dogs represent an animal model for the human EAST syndrome.